A Bioreactor Technology for Modeling Fibrosis in Human and Rodent Precision‐Cut Liver Slices. Issue 4 (28th May 2019) - Paish, Hannah L.; Reed, Lee H.; Brown, Helen; Bryan, Mark C.; Govaere, Olivier; Leslie, Jack; Barksby, Ben S.; Garcia Macia, Marina; Watson, Abigail; Xu, Xin; Zaki, Marco Y.W.; Greaves, Laura; et al.
Abstract : Precision cut liver slices (PCLSs) retain the structure and cellular composition of the native liver and represent an improved system to study liver fibrosis compared to two‐dimensional mono‐ or co‐cultures. The aim of this study was to develop a bioreactor system to increase the healthy life span of PCLSs and model fibrogenesis. PCLSs were generated from normal rat or human liver, or fibrotic rat liver, and cultured in our bioreactor. PCLS function was quantified by albumin enzyme‐linked immunosorbent assay (ELISA). Fibrosis was induced in PCLSs by transforming growth factor beta 1 (TGFβ1) and platelet‐derived growth factor (PDGFββ) stimulation ± therapy. Fibrosis was assessed by gene expression, picrosirius red, and α‐smooth muscle actin staining, hydroxyproline assay, and soluble ELISAs. Bioreactor‐cultured PCLSs are viable, maintaining tissue structure, metabolic activity, and stable albumin secretion for up to 6 days under normoxic culture conditions. Conversely, standard static transwell‐cultured PCLSs rapidly deteriorate, and albumin secretion is significantly impaired by 48 hours. TGFβ1/PDGFββ stimulation of rat or human PCLSs induced fibrogenic gene expression, release of extracellular matrix proteins, activation of hepatic myofibroblasts, and histological fibrosis. Fibrogenesis slowly progresses over 6 days in cultured fibrotic rat PCLSs without exogenous challenge. Activin receptor‐like kinase 5 (Alk5) inhibitor (Alk5i), nintedanib, and obeticholic acid therapy limited fibrogenesis in TGFβ1/PDGFββ‐stimulated PCLSs, and Alk5i blunted progression of fibrosis in fibrotic PCLS. Conclusion: We describe a bioreactor technology that maintains functional PCLS cultures for 6 days. Bioreactor‐cultured PCLSs can be successfully used to model fibrogenesis and demonstrate efficacy of antifibrotic therapies.